Export now : five keys to entering new markets - Lavin, Franklin L.; Cohan, Peter S., 1957- (Singapore ; Hoboken, NJ : John Wiley & Sons (Asia), 2011)
How your business can tap into foreign markets In Export Now, two superbly qualified authors explain the secrets to taking your company global. Offering a real-world strategy that any sized business can use to go global, this book serves as a trustworthy handbook for identifying, evaluating, and profiting from global business opportunities.
pt. 1. Why and what : setting your export goals -- pt. 2. How : five keys to choosing your export strategy -- pt. 3. When : making your export strategy happen.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Exports; Export marketing; Business enterprises -- Case studies; Exportations; Entreprises; BUSINESS & ECONOMICS -- Exports & Imports; BUSINESS & ECONOMICS -- International -- Marketing; BUSINESS & ECONOMICS -- Marketing -- Multilevel; Business enterprises; Export marketing; Exports; Case studies